2008
DOI: 10.1038/ng.187
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of multiple imprinted loci in individuals with transient neonatal diabetes is associated with mutations in ZFP57

Abstract: We have previously described individuals presenting with transient neonatal diabetes and showing a variable pattern of DNA hypomethylation at imprinted loci throughout the genome. We now report mutations in ZFP57, which encodes a zinc-finger transcription factor expressed in early development, in seven pedigrees with a shared pattern of mosaic hypomethylation and a conserved range of clinical features. This is the first description of a heritable global imprinting disorder that is compatible with life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
395
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 470 publications
(421 citation statements)
references
References 15 publications
13
395
0
13
Order By: Relevance
“…About 20% of patients with transient neonatal diabetes mellitus type 1 show loss of methylation at the PLAGL1/HYMAI ICR, which is normally maternally methylated (Figure 2 and Table 1). 54,55 Over 50% of these patients also show hypomethylation at other maternally methylated ICRs across the genome, which was recently found to be associated with ZFP57 mutations (Table 1). 54 The phenotype can be explained by defects in either establishment or maintenance of methylation imprints but, as noted above, studies on Zfp57 knock-out mice showed that its predominant role is in maintenance after fertilization.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 89%
See 1 more Smart Citation
“…About 20% of patients with transient neonatal diabetes mellitus type 1 show loss of methylation at the PLAGL1/HYMAI ICR, which is normally maternally methylated (Figure 2 and Table 1). 54,55 Over 50% of these patients also show hypomethylation at other maternally methylated ICRs across the genome, which was recently found to be associated with ZFP57 mutations (Table 1). 54 The phenotype can be explained by defects in either establishment or maintenance of methylation imprints but, as noted above, studies on Zfp57 knock-out mice showed that its predominant role is in maintenance after fertilization.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 89%
“…54,55 Over 50% of these patients also show hypomethylation at other maternally methylated ICRs across the genome, which was recently found to be associated with ZFP57 mutations (Table 1). 54 The phenotype can be explained by defects in either establishment or maintenance of methylation imprints but, as noted above, studies on Zfp57 knock-out mice showed that its predominant role is in maintenance after fertilization. 30 However, it is important to note that some individuals with hypomethylation at multiple ICRs carry no mutation in ZFP57, indicating the existence of other factors.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 89%
“…26,27,33 In addition, mutations in the ZFP57 gene result in transient neonatal diabetes mellitus type 1, possibly through Plagl1 overexpression. 34,35 The role of ZFP57 in tumorigenesis has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes encoding members of the zinc-finger protein family have been considered good candidates as causative defects of MLID, given the well-established role of ZFP57 mutation in patients with transient neonatal diabetes mellitus and MLID [26,27]. However, no mutations have been found to date in other members of the protein family in MLID patients.…”
Section: Introductionmentioning
confidence: 99%